2012
DOI: 10.3389/fnmol.2012.00079
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C in Alzheimer's disease

Abstract: Changes in expression and secretion levels of cystatin C (CysC) in the brain in various neurological disorders and in animal models of neurodegeneration underscore a role for CysC in these conditions. A polymorphism in the CysC gene (CST3) is linked to increased risk for Alzheimer's disease (AD). AD pathology is characterized by deposition of oligomeric and fibrillar forms of amyloid β (Aβ) in the neuropil and cerebral vessel walls, neurofibrillary tangles composed mainly of hyperphosphorylated tau, and neurod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
107
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 146 publications
(227 reference statements)
2
107
0
3
Order By: Relevance
“…It is interesting to note that a polymorphism (G73A) in cystatin C has been linked to AD (43). Furthermore, cystatin C is increased in regions around A␤ deposits in the AD brain (44,45), suggesting that it may play a role in pathogenesis or in response to A␤ pathology. Indeed, two groups, Mi et al (46) and Kaeser et al (47), found that cystatin C may have a protective effect as APP transgenic mice that had higher cystatin C expression were found to have diminished A␤ deposition.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that a polymorphism (G73A) in cystatin C has been linked to AD (43). Furthermore, cystatin C is increased in regions around A␤ deposits in the AD brain (44,45), suggesting that it may play a role in pathogenesis or in response to A␤ pathology. Indeed, two groups, Mi et al (46) and Kaeser et al (47), found that cystatin C may have a protective effect as APP transgenic mice that had higher cystatin C expression were found to have diminished A␤ deposition.…”
Section: Discussionmentioning
confidence: 99%
“…CysC plays a role in different diseases, from cancer to neurodegenerative disorders (66). Mutations of CysC can lead to fatal hereditary cystatin C amyloid angiopathy.…”
Section: Cystatin Cmentioning
confidence: 99%
“…CysC is thus likely indirectly involved in A␤ regulation. Epidemiologically, a polymor- phism in the CysC gene (CST3) has been linked to enhanced risk for AD (66), and CysC modulates cerebral ␤-amyloidosis in A␤PP transgenic mice (71).…”
Section: Cystatin Cmentioning
confidence: 99%
“…In addition, CST3 exerts a protective effect in AD by preventing the formation of toxic forms of Aβ (104). A previous study with transgenic mice demonstrated the association of CST3 with non-toxic forms of Aβ and prevention of Aβ plaque formation (105). In addition, the authors revealed that reduced levels of CST3 may impair the neuronal ability to prevent neurodegeneration in AD (105).…”
Section: Cystatin C (Cst3)mentioning
confidence: 99%